2017
DOI: 10.3389/fenvs.2017.00023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change Adaptation Strategies on Winter Wheat and Cropping System Performance across Precipitation Gradients in the Inland Pacific Northwest, USA

Abstract: Ecological instability and low resource use efficiencies are concerns for the long-term productivity of conventional cereal monoculture systems, particularly those threatened by projected climate change. Crop intensification, diversification, reduced tillage, and variable N management are among strategies proposed to mitigate and adapt to climate shifts in the inland Pacific Northwest (iPNW). Our objectives were to assess these strategies across iPNW agroecological zones and time for their impacts on (1) winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 120 publications
(111 reference statements)
2
12
0
Order By: Relevance
“…Precipitation can have both positive and negative effects on the variability of annual carbon and water budgets, depending on whether annual rainfall is sufficient or deficient in the region . In the semiarid iPNW region, our results showed that annual NEE, GPP, EXP, NECB, and ET during the winter wheat crop years increased with precipitation for both low-and high-rainfall zones, which was also reported in other studies (e.g., Biederman et al, 2016;Maaz et al, 2017;Sakalli et al, 2017;Zhang et al, 2016). For temperature effects, annual R eco positively varied with mean annual temperature only for CAF-NT.…”
Section: Climatic Condition Effects and Climate Change Implicationssupporting
confidence: 89%
“…Precipitation can have both positive and negative effects on the variability of annual carbon and water budgets, depending on whether annual rainfall is sufficient or deficient in the region . In the semiarid iPNW region, our results showed that annual NEE, GPP, EXP, NECB, and ET during the winter wheat crop years increased with precipitation for both low-and high-rainfall zones, which was also reported in other studies (e.g., Biederman et al, 2016;Maaz et al, 2017;Sakalli et al, 2017;Zhang et al, 2016). For temperature effects, annual R eco positively varied with mean annual temperature only for CAF-NT.…”
Section: Climatic Condition Effects and Climate Change Implicationssupporting
confidence: 89%
“…They observed that the postharvest soil water content (105-120 cm) in an eroded ridgetop profile with shallow RRD was 28% higher than a nonrestricted profile at the same depth. Maaz et al (2017) suggested that a plateau in winter wheat yields with increasing annual precipitation in the eastern Palouse may be due to lower water-infiltration efficiency and lower subsoil water extraction. In a controlled column study, Nosalewicz and Lipiec (2014) found lower cumulative water uptake from deep layers in the column where soils were sufficiently dense to limit root-length density.…”
Section: Effect Of Root Restriction On Stored Soil Water Usementioning
confidence: 99%
“…For instance, Appendix I included so many soil quality indexes different from a study to another, such as Cation Exchange Capacity (CEC), Sodium Adsorption Ratio (SAR), Albeit the difference in methodologies and indicators, the practices assessed (i.e. tillage practices, mulching techniques, and soil amendments) showed positive impacts in terms of soil quality and health improvements, which are more eminent under extreme weather conditions [87][88][89][90]. However, the reference system in comparison is to be carefully selected [91]; for instance, comparing the impacts of organic amendments on yield increase when the control is a high input system would not be in favour of the organic amendments.…”
Section: Soil Managementmentioning
confidence: 99%